2022
DOI: 10.3389/fpsyt.2022.837846
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Anxiety Symptoms and Chinese Adolescents' Mental Health During the COVID-19 Pandemic: The Protective Role of Adolescents' Self-Compassion

Abstract: The COVID-19 outbreak triggered dramatic changes to family life. Parents, especially mothers, were found to experience more psychological distress during the pandemic, which may have had an impact on their children's mental health. The primary goal of this study was to examine the potential protective role of adolescents' self-compassion in the relationship between maternal anxiety and adolescents' mental health during the COVID-19 pandemic. Participants included 5,720 adolescents (48.9% girls; Mage = 11.60, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Some investigated the impact of an online intervention program on anxiety and depression levels, as well as physical symptoms, in frontline nurses fighting the COVID-19 pandemic to provide an empirical basis for crisis psychological interventions for frontline medical staff ( He et al, 2022 ). Some found that parents, especially mothers, experienced more psychological stress during the outbreak, which may have had an impact on their children’s mental health, while adolescents with higher levels of self-compassion were less psychologically affected by their mothers’ anxiety ( Zhou et al, 2022 ).…”
Section: Research Backgroundmentioning
confidence: 99%
“…Some investigated the impact of an online intervention program on anxiety and depression levels, as well as physical symptoms, in frontline nurses fighting the COVID-19 pandemic to provide an empirical basis for crisis psychological interventions for frontline medical staff ( He et al, 2022 ). Some found that parents, especially mothers, experienced more psychological stress during the outbreak, which may have had an impact on their children’s mental health, while adolescents with higher levels of self-compassion were less psychologically affected by their mothers’ anxiety ( Zhou et al, 2022 ).…”
Section: Research Backgroundmentioning
confidence: 99%
“…Similarly, studies conducted during the surging period of COVID-19 in Italy showed that parental active coping was positively associated with young children's adaptive behaviors ( Petrocchi et al, 2020 ), and poorer quality of parent-child relationship was associated with higher levels of psychopathological symptoms among adolescents ( Cimino and Cerniglia, 2021 ). A recent study from China provided comparable results that adolescents' negative affect, PTSD symptoms, anxiety, and depression during the initial outbreak of the pandemic were related to maternal anxiety ( Zhou et al, 2022 ).…”
Section: Introductionmentioning
confidence: 98%
“…According to cognitive theory, a lack of self-compassion may lead to negative emotions and self-denial, further affecting the development of depression ( Beck, 1964 ). Self-kindness and mindfulness are important components of self-compassion, and they can help individuals remain caring and accepting of themselves, which can alleviate depression ( Kuyken et al, 2010 ; Joeng et al, 2017 ; Kurebayashi, 2020 ; Zhou et al, 2022 ). In conclusion, studies have shown significant correlations between self-compassion and sleep quality.…”
Section: Introductionmentioning
confidence: 99%